International Business Logistics Journal “IBL” - Sara H. Elgazzar (International Business Logistics Journal)
Logistics research and applications are more important today than ever before. Logistics has achieved greater prominence within the business with increased awareness of its operational, strategic, and financial impact on business success. Logistics functions such as warehousing, inventory management, transportation modeling, and other logistics facilities have brought large towns and cities closer together.